2020
DOI: 10.1523/jneurosci.2374-19.2020
|View full text |Cite
|
Sign up to set email alerts
|

Cortical and Subcortical Effects of Transcutaneous Spinal Cord Stimulation in Humans with Tetraplegia

Abstract: An increasing number of studies supports the view that transcutaneous electrical stimulation of the spinal cord (TESS) promotes functional recovery in humans with spinal cord injury (SCI). However, the neural mechanisms contributing to these effects remain poorly understood. Here we examined motor-evoked potentials in arm muscles elicited by cortical and subcortical stimulation of corticospinal axons before and after 20 min of TESS (30 Hz pulses with a 5 kHz carrier frequency) and sham-TESS applied between C5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
163
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 96 publications
(176 citation statements)
references
References 61 publications
9
163
1
3
Order By: Relevance
“…In our study, the increase in peak-to-peak Q and TA MEP amplitude was not maintained up to 2 and 4 min after tSCS. In contrast in a recent study a 20-min single session of tSCS increased the amplitude of subcortical motor evoked responses in arm muscles of people with a high level of SCI for up to 75 min [ 27 ]. Moreover, other studies have identified prolonged post intervention effects of tSCS based on improvement of spasticity [ 13 ] or the subjective perception of voluntary movement [ 8 ].…”
Section: Discussionmentioning
confidence: 90%
See 4 more Smart Citations
“…In our study, the increase in peak-to-peak Q and TA MEP amplitude was not maintained up to 2 and 4 min after tSCS. In contrast in a recent study a 20-min single session of tSCS increased the amplitude of subcortical motor evoked responses in arm muscles of people with a high level of SCI for up to 75 min [ 27 ]. Moreover, other studies have identified prolonged post intervention effects of tSCS based on improvement of spasticity [ 13 ] or the subjective perception of voluntary movement [ 8 ].…”
Section: Discussionmentioning
confidence: 90%
“…This is the first study to identify a selective effect of tSCS on Q MEPs compared to distal lower limb muscles such as the TA. Recently, an effect of non-invasive spinal stimulation applied at 30 Hz pulses, with a 5 kHz carrier frequency, has been identified on MEPs recorded from the upper limb muscles following TMS in cases of cervical spinal cord injury [ 27 ]. Previously low frequency stimulation of afferents has been shown to increase corticospinal excitability in the upper limb [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations